IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN ANGKUTAN ORANG DENGAN KENDARAAN BERMOTOR UMUM DALAM TRAYEK (Kasus Bus Trans Anggrek di Kota Tangerang Selatan) - Larasati, Dinda; Kismartini, Kismartini; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
South Tangerang City is a part of the metropolitan area favored by many Indonesians, particularly commuters. Consequently, it is essential for the city to provide adequate public transportation to facilitate access to various destinations. However, only about 36.2% of the city's population is currently served by public transportation. South Tangerang City has an urban public transportation system known as Bus Trans Anggrek, implemented by the city government to enhance mobility and comply with Ministry of Transportation Regulation No. 15 of 2019, which mandates local governments to ensure the availability of public transportation for their citizens. Despite this, the service has not been able to attract significant interest from the public, as evidenced by the low number of passengers. This study employs a descriptive qualitative method to analyze the implementation of the public transportation policy for Bus Trans Anggrek in South Tangerang City, along with its driving and inhibiting factors. The findings reveal that the implementation of the Bus Trans Anggrek policy is not yet optimal due to several issues. Although the policy aligns with the objectives outlined in Article 38 of Ministry of Transportation Regulation No. 15 of 2019, it has not been fully implemented according to the specified standards. The inhibiting factors identified include inadequacies in policy, implementation, target, environment, process, and utilization.